Dental patterning in the earliest sharks: Implications for tooth evolution. (18th December 2013) - Maisey, John G.; Turner, Susan; Naylor, Gavin J.P.; Miller, Randall F.
ABSTRACT Doliodus problematicus is the oldest known fossil shark‐like fish with an almost intact dentition (Emsian, Lower Devonian, c. 397Ma). We provide a detailed description of the teeth and dentition in D. problematicus, based on tomographic analysis of NBMG 10127 (New Brunswick Museum, Canada). Comparisons with modern shark dentitions suggest that Doliodus was a ram‐feeding predator with a dentition adapted to seizing and disabling prey. Doliodus provides several clues about the early evolution of the "shark‐like" dentition in chondrichthyans and also raises new questions about the evolution of oral teeth in jawed vertebrates. As in modern sharks, teeth in Doliodus were replaced in a linguo‐labial sequence within tooth families at fixed positions along the jaws (12–14 tooth families per jaw quadrant in NBMG 10127). Doliodus teeth were replaced much more slowly than in modern sharks. Nevertheless, its tooth formation was apparently as highly organized as in modern elasmobranchs, in which future tooth positions are indicated by synchronized expression of shh at fixed loci within the dental epithelium. Comparable dental arrays are absent in osteichthyans, placoderms, and many "acanthodians"; a "shark‐like" dentition, therefore, may be a synapomorphy of chondrichthyans and gnathostomes such as Ptomacanthus. The upper anterior teeth in Doliodus were not attached to the palatoquadrates, but were instead supported by the ethmoid region of the prechordal basicranium, as in some other Paleozoic taxa (e.g., Triodus, Ptomacanthus). This suggests that the chondrichthyan dental lamina was originally associated with prechordal basicranial cartilage as well as jaw cartilage, and that the modern elasmobranch condition (in which the oral dentition is confined to the jaws) is phylogenetically advanced. Thus, oral tooth development in modern elasmobranchs does not provide a complete developmental model for chondrichthyans or gnathostomes. J. Morphol. 275:586–596, 2014. © 2013 Wiley Periodicals, Inc.